2007
DOI: 10.1074/jbc.m701042200
|View full text |Cite
|
Sign up to set email alerts
|

Werner Helicase-interacting Protein 1 Binds Polyubiquitin via Its Zinc Finger Domain

Abstract: DNA repair is regulated on many levels by ubiquitination. In order to identify novel connections between DNA repair pathways and ubiquitin signaling, we used mass spectrometry to identify proteins that interact with lysine 6-linked polyubiquitin chains. From this proteomic screen, we identified the DNA repair protein WRNIP1 (Werner helicase-interacting protein 1), along with nucleosome assembly protein 1, as novel ubiquitin-interacting proteins. We found that a small zinc finger domain at the N terminus of WRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 55 publications
5
98
0
3
Order By: Relevance
“…It has been recently shown that Wrnip1 can bind to poly-but not mono-ubiquitin (12). To validate these findings, we fused the amino acids 9 -48 spanning the UBZ domain of human Wrnip1 in-frame with GST, expressed such fusion in E. coli, and used it to pull down a mixture of Ub chains varying in length from 2 to 7 monomers, linked either via lysine 48 or 63.…”
Section: Wrnip1 Can Interact With Both Mono-and Poly-ubiquitin-mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently shown that Wrnip1 can bind to poly-but not mono-ubiquitin (12). To validate these findings, we fused the amino acids 9 -48 spanning the UBZ domain of human Wrnip1 in-frame with GST, expressed such fusion in E. coli, and used it to pull down a mixture of Ub chains varying in length from 2 to 7 monomers, linked either via lysine 48 or 63.…”
Section: Wrnip1 Can Interact With Both Mono-and Poly-ubiquitin-mentioning
confidence: 99%
“…We focused our attention on Wrnip1/Mgs1, which was recently shown to selectively bind poly-Ub chains and regulate the turnover of ubiquitylated proteins (12). Wrnip1 has been genetically linked to the ubiquitin ligase Rad18 in yeast and chicken cells and proposed to function in response to stalling of DNA replication forks (8,18,19).…”
Section: Wrnip1 Can Interact With Both Mono-and Poly-ubiquitin-mentioning
confidence: 99%
See 1 more Smart Citation
“…The protein contains a RING domain, essential for its ubiquitin ligase activity, 22 a ubiquitin-binding zinc finger (UBZ) motif 23,24 and a SAP domain, which has been shown to mediate DNA binding in many other proteins. 25,26 Recently, the DNA-binding properties of hRad18 have been characterized in detail.…”
Section: Rad18 Ssdna-binding Is Highly Sensitive To Ionic Strengthmentioning
confidence: 99%
“…33 WHIP may be a modulator for initiation or re-initiation events during DNA polymerase delta-mediated DNA synthesis and with an intrinsic ATPase activity that may function as a sensor of DNA damage or of arrested replication forks and regulates the extent of DNA synthesis. 36,43,44 Mutations of the yeast WHIP homologue, MGS1 (maintenance of genome stability 1), can enhance the accelerated aging process in budding yeast. 34,45,46 The present investigation was undertaken to substantiate the interaction of WHIP with the NPC, followed by visualization of WHIP at the NE.…”
Section: Introductionmentioning
confidence: 99%